Determinasi Kepatuhan Wajib Pajak Usaha Mikro Kecil Menengah (UMKM) DI KOTA SEMARANG - Laelatul Qodariyah; Parju Parju (FEB UNTAG Semarang, 2020)
This study aims to analyze the influence of understanding tax regulations, tax sanctions, tax awareness on tax compliance of SMEs in the city of Semarang. The data used are primary data in the form of a questionnaire (questionnaire) using a Likert scale. The sample used in this study were 100 respondents with calculated using the Slovin formula. The sampling method used in this study is cluster random sampling (regional sampling technique). Analysis of the data used by researchers is multiple linear regression analysis with SPSS application The results showed that the understanding of taxation regulations had a positive and significant effect on the compliance of MSME taxpayers with a β value of 0.512 and a significance value of 0,000. Tax sanctions have a positive and not significant effect on MSME taxpayer compliance with a β2 value of 0.149 and a significance value of 0.121. Tax awareness has a positive and insignificant effect on MSME taxpayer compliance with a β3 value of 0.194 and a significance value of 0.077.Keywords: Understanding of Taxation Regulations, Tax Sanctions, Tax Awareness, Taxpayer Compliance